2015
DOI: 10.1002/pssb.201552584
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectrum and excitons in bulk and monolayer MX2 (M=Zr, Hf; X=S, Se)

Abstract: Abstractauthoren We present first principles calculations of the electronic and optical properties of bulk and monolayer structures for four transition metal chalcogenides, MX2 false(M=Zr and Hf; X=S, Se), using a post density functional many‐body perturbation GW approximation in conjunction with the Bethe–Selpeter approximation (GW‐BSE). Optical absorption spectra predict the presence of a strongly bound exciton that lies below the direct band gap in two bulk (HfS2 and ZrSe2) and in all the monolayer structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 70 publications
6
26
0
Order By: Relevance
“…However, there exists the difference of approximate 0.44, 0.10, 0.08, and 0.01 eV for ZrS 2 , ZrSe 2 , HfS 2 , and HfSe 2 , respectively, when comparing the results with that of Ref. [28]. The difference could result from the different ground state structures of IVB-VIA TMDs or pseudopotentials used for the calculations.…”
Section: Electronic Propertiesmentioning
confidence: 86%
“…However, there exists the difference of approximate 0.44, 0.10, 0.08, and 0.01 eV for ZrS 2 , ZrSe 2 , HfS 2 , and HfSe 2 , respectively, when comparing the results with that of Ref. [28]. The difference could result from the different ground state structures of IVB-VIA TMDs or pseudopotentials used for the calculations.…”
Section: Electronic Propertiesmentioning
confidence: 86%
“…On the other hand, ZrX 2 (X = S, Se) are the group IVB TMDC materials that crystallized in one-layer trigonal (1T) structure of CdI 2 type [12]. These materials also have band gaps ranging from 1.1 to 2 eV [13,14]. The compounds usually possess high conductivity and contains defects and surface states in its layer structure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Particularly, it was demonstrated that nanotubes produced from layered transition metal disulfides MoS 2 and WS 2 exhibit a stable, closed, hollow structure. [6,9,10] The theoretical modeling was carried out in references [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] for bulk Zr(Hf) sulfides and their monolayers. [4,7,8] The ZrS 2 and HfS 2 nanotubes have been synthesized since the early 2000s.…”
Section: Introductionmentioning
confidence: 99%